A Feasibility Study of Implantable Loop Recorder Monitoring Capacity in Older Fallers - Bourke, Robert Henry (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2025)
INTRODUCTION: Falls are one of the most common causes of injury, prolonged hospitalisation, increased dependency and residential care admission amongst older people. There is a known association between cardiovascular disorders and falls. This thesis begins with a systematic review and meta-analysis to explore this relationship in detail. It then highlights gaps in current monitoring methods and introduces the potential of implantable loop recorders (ILRs) with an embedded triaxial accelerometers to provide detailed biophysiological data. METHODS: The study comprises three validation studies aimed at interpreting data from ILRs with triaxial accelerometers. Subsequently, a clinical trial involving thirty 30 participants investigates the correlation between arrhythmias detected by ILRs and incidents of falls. Finally, a retrospective analysis of biophysiological parameters is performed to determine if certain changes or patterns may be predictive of falls. RESULTS: The validation studies demonstrate robust interpretation of triaxial accelerometer data from ILRs, confirming their efficacy in capturing certain relevant physiological events. Analysis from the clinical trial demonstrates the ability of ILRs to detect significant arrhythmias in older fallers. Biophysiological parameters were not found to be related to falls. CONCLUSIONS: This thesis highlights the potential of ILRs with triaxial accelerometers in monitoring physiological parameters in community dwelling older adults. While successful in detecting arrhythmias linked to falls, early physiological changes in gait, posture, and cardiac data were found insufficient predictors of future falls. Future research should focus on enhancing predictive models and exploring additional physiological parameters to improve fall risk assessment using ILRs.
APPROVED
Keywords: Falls; Arrhythmia; ILR; Gait; Cardiovascular; Older Adults; Syncope; Implantable Loop Recorder